2019
DOI: 10.1021/acsmacrolett.9b00607
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Chain Folding in Polymer Single Crystals by Single-Molecule Force Spectroscopy

Abstract: Chain folding is a motif of polymer crystallization, which is essential for determining the crystallization kinetics. However, the experimental quantification of the chain folding remains a challenge because of limited instrumental resolution. Here, we quantify chain folding in solution-grown single crystals by using atomic force microscopy (AFM)-based single-molecule force spectroscopy. The fingerprint spectrum of force-induced chain motion allows us to decipher the adjacent and nonadjacent re-entry folding w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…The fingerprint spectrum of force‐induced chain motion allows to decipher the adjacent and nonadjacent re‐entry folding with spatial resolution of subnanometers. The average fraction of adjacent re‐entry folds was determined as 91–95% for PLLA, supporting the adjacent re‐entry model for solution‐grown single crystals 87 …”
Section: Thermodynamics and Kinetics Of Secondary Nucleationsupporting
confidence: 68%
See 1 more Smart Citation
“…The fingerprint spectrum of force‐induced chain motion allows to decipher the adjacent and nonadjacent re‐entry folding with spatial resolution of subnanometers. The average fraction of adjacent re‐entry folds was determined as 91–95% for PLLA, supporting the adjacent re‐entry model for solution‐grown single crystals 87 …”
Section: Thermodynamics and Kinetics Of Secondary Nucleationsupporting
confidence: 68%
“…For example, in solution‐grown PLLA crystals, the average number of chain‐folds is 7 under the assumption of full adjacent re‐entry structure, 84,85 whereas the number is only 1.5–2 when crystallized from the melt 86 . Zhang et al 87 established a method to quantify the chain folding in polymer single crystals by using AFM‐based single‐molecule force spectroscopy. The fingerprint spectrum of force‐induced chain motion allows to decipher the adjacent and nonadjacent re‐entry folding with spatial resolution of subnanometers.…”
Section: Thermodynamics and Kinetics Of Secondary Nucleationmentioning
confidence: 99%
“…Hence, the increased thickness of the long period of the crystals is a strong indication, that even the solution grown crystals still contain some part of random reentry folds. As has been shown by NMR 44,[49][50][51] and AFM 52 solution grown crystals can have up to 10%, whereas melt grown crystals exhibit up to 35% of random reentry folds. In the case of the PPEs synthesized in this work, we can therefore assume that a certain amount of random reentry folding is also present in the solution-grown crystals.…”
Section: Solid-state Characterizationmentioning
confidence: 72%
“…studied the chain folding structures of solution‐grown single crystals by AFM‐based single‐molecule force spectroscopy and concluded that the average fractions of adjacent re‐entry folds were 91–95%. [ 34 ] The predominantly intramolecular folding in the Langmuir monolayer is similar to the solution‐grown crystals.…”
Section: Resultsmentioning
confidence: 85%